Childhood Stunting in Tajikistan : Quantifying the Association with WASH, Food Security, Health, and Care Practices - Lavado, Rouselle; Seitz, William; Thiebaud, Alessia (World Bank, Washington, DC, 2018)
More than 20 percent of children under the age of 5 in Tajikistan are stunted. A large literature finds that stunting and undernutrition in early childhood are commonly the result of several contributing environmental, food, hygiene, and health-related factors. However, quantifying these interactions is usually not possible due to the difficulty of collecting sufficient data on each dimension in a single survey. To address this issue, we integrated the samples of two separate nationally representative surveys conducted simultaneously in Tajikistan in late 2016. This design allows analysis of the determinants of undernutrition in a unified framework. The results show strong associations between undernutrition and the number of food calories consumed, food diversity, access to water, sanitation and hygiene (WASH) services, access to health services, and care practices. Consistent with previous studies, the results also show that overlapping adequacies are associated with much reduced stunting risk. The findings suggest that: i) nutritioninterventions addressing multiple risk factors may promote better outcomes than focusingon any single deprivation, ii) there is need for programs addressing food inadequacy, bothin the form of the number of calories consumed and the diversity of food consumed, iii)promoting food adequacy alone is likely not sufficient to generate large reductions inmalnutrition, and iv) interventions should predominantly focus on rural areas where risksof malnutrition are substantially higher.